A third term for FDR : the election of 1940 - Jeffries, John W., 1942- (UPCC book collections on Project MUSE., 2017)
The 1940 presidential election was the first election that featured a sitting president running for a third term. It was also an election conducted in the midst of a growing world war and debates over the involvement of the United States.